Phase 2 study of efgartigimod, a novel FcRn antagonist, in adult patients with primary immune thrombocytopenia. Issue 2 (10th December 2019) - Newland, Adrian C.; Sánchez‐González, Blanca; Rejtő, László; Egyed, Miklos; Romanyuk, Nataliya; Godar, Marie; Verschueren, Katrien; Gandini, Domenica; Ulrichts, Peter; Beauchamp, Jon; Dreier, Torsten; Ward, E. Sally; et al.
Abstract: Primary immune thrombocytopenia (ITP) is an acquired autoimmune bleeding disorder, characterized by a low platelet count (<100 × 10 9 /L) in the absence of other causes associated with thrombocytopenia. In most patients, IgG autoantibodies directed against platelet receptors can be detected. They accelerate platelet clearance and destruction, inhibit platelet production, and impair platelet function, resulting in increased risk of bleeding and impaired quality of life. Efgartigimod is a human IgG1 antibody Fc‐fragment, a natural ligand of the neonatal Fc receptor (FcRn), engineered for increased affinity to FcRn, while preserving its characteristic pH‐dependent binding. Efgartigimod blocks FcRn, preventing IgG recycling, and causing targeted IgG degradation. In this Phase 2 study, 38 patients were randomized 1:1:1 to receive four weekly intravenous infusions of either placebo (N = 12) or efgartigimod at a dose of 5 mg/kg (N = 13) or 10 mg/kg (N = 13). This short treatment cycle of efgartigimod in patients with ITP, predominantly refractory to previous lines of therapy, was shown to be well tolerated, and demonstrated a favorable safety profile consistent with Phase 1 data. Efgartigimod induced a rapid reduction of total IgG levels (up to 63.7% mean change from baseline), which was associated with clinically relevant increases in platelet counts (46% patients on efgartigimod vs 25% on placebo achieved a platelet count of ≥50 × 10 9 /L on at least two occasions, and 38% vs 0% achieved ≥50 × 10 9 /L for at least 10 cumulative days), and a reduced proportion of patients with bleeding. Taken together, these data warrant further evaluation of FcRn antagonism as a novel therapeutic approach in ITP.